Oral History Program Interview: James E. Lambert, Jr. - Lambert, James E. Jr.
Lambert was born in Pleasant Valley, Garvin County, Oklahoma in 1924. He and his family came to Pumpkin Center, California on September 11, 1928. Lambert recalls the meaning of "Okie," how Californians mistreated migrants, the grassroots organizing for strikes against growers, how child work-permits affected anyone under fourteen finding work, examples of home remedies, the transition form animal powered to machine powered farm equipment, what it was like living in a county camp, and a significant woman doctor in Wasco.